Paradise falls: the true story of an environmental catastrophe - O'Brien, Keith (Pantheon Books, 2022)
"From the New York Times best-selling journalist, the staggering, hidden story of an unlikely band of mothers who discovered the deadly secret of Love Canal, and exposed one of America's most devastating environmental disasters. Lois Gibbs, Luella Kenny and Barbara Quimby thought they had found a slice of the American dream when they and their families moved onto the quiet streets of Love Canal, a picturesque middle-class hamlet by Niagara Falls in the winter of 1977, the town had record snowfalls, and in the spring, rains filled the earth with water like a sponge and the basements of the neighborhood's homes with a pungent odor. It was the sweet, synthetic smell of chemicals. Then, one by one, the children of the more than 800 families that made Love Canal their home started getting very sick. In this propulsive work of narrative reportage, Keith O'Brien uncovers how Lois, Luella, Barbara and other local mothers uncovered the poisonous secret of Love Canal: that they were living on the site where industrial employer Hooker Chemical had been dumping toxic waste for years, and covering it up. O'Brien braids together the previously unknown stories of Hooker Chemical's deception, the local newspapermen and scientists who tried to help, the city officials who didn't, and the heroic women who stood up to corporate and governmental indifference, and-ultimately-triumphed. O'Brien paints a vividly how their dauntless efforts would capture the American imagination at the time and form the foundation of the modern environmental movement"--